Patients with severe factor XI deficiency have a reduced incidence of deep-vein thrombosis - Salomon, Ophira; Steinberg, David M.; Zucker, Michal; Varon, David; Zivelin, Ariella; Seligsohn, Uri (Thrombosis and Haemostasis, 2011)
Factor XI (FXI) plays a dual role in haemostasis and thrombosis. It contributes to thrombin generation and promotes inhibition of fibrinolysis. Severe FXI deficiency was shown to confer protection against arterial and venous thrombosis in animal models without compromising haemostasis. We have previously shown that patients with severe FXI deficiency have a low incidence of ischaemic stroke, but display the usual incidence of myocardial infarction. In the present study, we compared the incidence of deep-vein thrombosis (DVT) in 219 unrelated patients with severe FXI deficiency aged 20–94 to the incidence in a large population-based study. No cases of DVT were observed in the FXI-deficient cohort, a result that is significantly lower than the expected number (4.68) computed from the population-based study. The low incidence remains statistically significant when compared to three other population-based studies. These data suggest that severe FXI deficiency provides protection against DVT.
Keywords: Factor XI; factor XI deficiency; deep-vein thrombosis